STRATEGIES AND TOOLS FOR HYBRID CONFLICTS RESOLUTION IN XXI CENTURY (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
The system of international relations in the 21st century increasinglyredefines several key geopolitical concepts. The global geopoliticalmodel today is also being reshaped on international level. Along withthese new geopolitical trends, new interpretations of concepts such aswar, conflict, and use of force have emerged. The main purpose of thispaper is to analyze the tools and strategies for resolving the so-called"hybrid conflicts". The main thesis of the research is that in order toresolve such a conflict it is necessary to apply the whole set ofinstruments at both military and strategic level. Otherwise, this type ofconflict can be a serious threat to the national security of each country.To prove his thesis, the article sets the following tasks. First, to analyzethe concept of hybrid conflict and clarify its essence. Second, tosystematize the main geopolitical aspects of the hybrid conflicts. Third,to launch possible techniques and strategies for the resolution of hybridconflicts. From a methodological point of view, the article builds onempirical data acquired on the basis of exploring different practices inresolving hybrid conflicts.